Comparative effectiveness of dimethyl fumarate in multiple sclerosis. Issue 3 (8th October 2021) - Bosco‐Lévy, Pauline; Debouverie, Marc; Brochet, Bruno; Guillemin, Francis; Louapre, Céline; Maillart, Elisabeth; Heinzlef, Olivier; Lignot, Séverine; Diez, Pauline; Abouelfath, Abdelilah; Lassalle, Régis; Blin, Patrick; et al.
Abstract : Aims: To assess the effectiveness of dimethyl fumarate (DMF) on annual rate of relapse subject to treatment (ARRt) and disability progression in multiple sclerosis (MS) compared to injectable immunomodulators (IMM), teriflunomide (TERI) and fingolimob (FTY), in real‐life setting. Methods: A population‐based cohort study was conducted using data of the French nationwide claims database, SNDS. All patients initiating IMM, TERI, FTY or DMF between 1 July 2015 and 12 December 2017, with 4.5 years of database history and 1–3.5 years of follow‐up were included in this study. DMF patients were 1:1 matched to IMM, TERI or FTY using a high dimensional propensity score. Negative binomial regression and a logistic regression model were used to estimate the relative risk (RR ± [95% CI]) of ARRt and the odds ratio (OR ± [95% CI]) of disability progression, respectively. Results: Overall, 9304 subjects were identified: 29.0% initiated DMF, 33.2% TERI, 5.6% FTY and 32.2% an IMM. The matched cohorts consisted of 1779 DMF‐IMM patients, 1679 DMF‐TERI patients, and 376 DMF‐FTY patients. DMF significantly reduced ARRt compared to IMM (RR 0.72 [0.61–0.86]) and TERI (0.81 [0.68–0.96]) and did not show any significant difference when compared with FTY. The risk of the progression of MS‐specific disability was not significantly different for any matched cohorts. Conclusion: DMF is associated with lower risk of treated relapse for patients with RRMS than other first‐line RRMS agents (TERI and IIM).